2001
DOI: 10.1136/jmg.38.2.102
|View full text |Cite
|
Sign up to set email alerts
|

De novo recurrent germline mutation of the BRCA2 gene in a patient with early onset breast cancer

Abstract: Germline mutations in either of the two major breast cancer predisposition genes, BRCA1 and BRCA2, account for a significant proportion of hereditary breast/ ovarian cancer. Identification of breast cancer patients carrying mutations of these genes is primarily based on a positive family history of breast/ovarian cancer or early onset of the disease or both. In the course of mutation screening of the BRCA1 and BRCA2 genes in a hospital based series of patients with risk factors for hereditary breast/ovarian ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
24
2

Year Published

2006
2006
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 10 publications
3
24
2
Order By: Relevance
“…The result suggests a de novo event in a testicular germ cell, although an occurrence in the zygote can not be discarded. This is in agreement with previous findings in de novo mutations in BRCA1 and BRCA2, in which the paternal origin could be ascertained [5,8], and also in other hereditary cancer syndromes (neurofibromatosis type 1, MEN2B and retinoblastoma) [10,11]. It has been suggested that the origin of new mutations may be influenced by both genomic imprinting effects and the increased number of cell divisions in spermatogenesis compared with oogenesis.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…The result suggests a de novo event in a testicular germ cell, although an occurrence in the zygote can not be discarded. This is in agreement with previous findings in de novo mutations in BRCA1 and BRCA2, in which the paternal origin could be ascertained [5,8], and also in other hereditary cancer syndromes (neurofibromatosis type 1, MEN2B and retinoblastoma) [10,11]. It has been suggested that the origin of new mutations may be influenced by both genomic imprinting effects and the increased number of cell divisions in spermatogenesis compared with oogenesis.…”
Section: Discussionsupporting
confidence: 88%
“…Despite the high number of mutations identified and the large number of studies carried out world wide, to our knowledge there is only one published report of a de novo mutation in BRCA1 [6] and three in BRCA2 [7][8][9].…”
Section: Introductionmentioning
confidence: 70%
See 1 more Smart Citation
“…The exact number of individuals with a BRCA1 or BRCA2 mutation that has occurred as a de novo event is not known but is believed to be small. [167][168][169] Risk to siblings of a proband with a BRCA1/2 mutation The risk to full siblings of an individual with a mutation in BRCA1 or BRCA2 depends on the genetic status of their parents. If one parent has the BRCA1 or BRCA2 mutation, then the risk for siblings to also carry the family-specific mutation is 50%.…”
Section: Risk To Parents Of a Proband With A Brca1/2 Mutationmentioning
confidence: 99%
“…3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 9 These mutations also contribute to clarify the workflow to launch in Spanish families, reducing costs and accelerating the diagnosis in high risk BOC families. Based on these results, we can define a panel of four BRCA2 Spanish proven founder mutations together with the highly prevalent BRCA2-3036delACAA (a priori of multiple origin) [18] that would allow to identify nearly 50% of BRCA2+ families with only 5 PCR reactions. Furthermore, in these mutations associated with early breast cancer it is essential to detect rapidly asymptomatic carriers who may benefit from prevention protocols since survival rates of breast cancer are worse than in older women.…”
Section: Discussionmentioning
confidence: 99%